Loculations and Associated Risk Factors of Childhood Pleural Tuberculosis - Wang, Jun-Li; Zhou, Ming; Zhang, Yan-An; Wang, Mao-Shui (Frontiers in Pediatrics, 2021)
Background: Pleural loculation in childhood pleural tuberculosis (TB) remains a problem in practice, it is usually associated with failure drainage. Therefore, to improve the management of childhood pleural TB, a retrospective study was conductedto identify the risk factors associated with loculated effusion in childhood pleural TB. Methods: Between January 2006 and December 2019, consecutive children (≤ 15 years old) with tuberculous pleural effusion (definite and possible) were included for further analysis. The demographic, clinical, laboratory, and radiographic features were collected from the medical records. Univariate and multivariate logistic regressions were used to explore the factors associated with the presence of pleural loculation in children with pleural TB. Results: A total of 154 children with pleural TB (definite, 123 cases; possible, 31 cases) were included in our study and then were classified as loculated effusion (n=27) and non-loculated effusion (n=127) groups by chest X-ray or ultrasonography. Multivariate analysis revealed that male gender (age-adjusted OR=3.903, 95% CI: 1.201, 12.683), empyema (age-adjusted OR=4.499, 95% CI: 1.597, 12.673), peripheral monocytes ≤0.46×109/L (age-adjusted OR=4.122, 95% CI: 1.518, 11.193) were associated with the presence of loculated effusion in children with pleural TB. Conclusion: In conclusion, several characteristics, such as male gender, empyema, and peripheral monocyte count have been identified as risk factors for pleural loculation in children with pleural TB. Our findings may be helpful to improve the management of pleural loculation in childhood pleural TB.